Adjusted multiple gases in the plasma flow induce differential antitumor potentials of plasma‐activated solutions. Issue 10 (10th July 2020) - Nakamura, Kae; Yoshikawa, Nobuhisa; Yoshihara, Masato; Ikeda, Yoshiki; Higashida, Akihiro; Niwa, Akihiro; Jindo, Takahiro; Tanaka, Hiromasa; Ishikawa, Kenji; Mizuno, Masaaki; Toyokuni, Shinya; Hori, Masaru; et al.
Abstract: We present a novel plasma system that can generate a plasma‐activated medium by changing the proportion of reactive gases such as oxygen, nitrogen, and hydrogen in the plasma flow. The correlation between the biological activity of plasma‐activated solutions prepared under multiple plasma gas‐flow conditions was evaluated. Mixed nitrogen, in addition to oxygen, in the gas flow is most powerful for producing plasma‐activated Ringer's lactate solution against antitumor effects on ovarian cancer cells as compared with oxygen or nitrogen alone. The antitumor effect of plasma‐activated solutions is controllable by the modification of the proportion of reactive gases (especially nitrogen and oxygen gases) in the plasma flow. These results suggest that the plasma flow conditions may be one of the candidates for the specifications of the plasma‐activated solutions to the therapeutic effect. Abstract :